Characterization of the role of KSHV ORF42 in viral replication and gene expression. - Butnaru, Matthew. (Tufts University. Tisch Library., 2019)
Kaposi's sarcoma-associated herpesvirus, the etiologic agent of Kaposi's sarcoma and other aggressive AIDS-associated malignancies, encodes over 90 genes, most of which are expressed only during the lytic replication cycle. The role of many of the KSHV lytic proteins in the KSHV replication cycle remains unknown, and many proteins are annotated based on known functions of homologs in other herpesviruses. Here I investigate the role of the previously uncharacterized KSHV lytic protein ORF42, a presumed tegument protein. I find that ORF42 is dispensable for reactivation from latency, but is required for efficient production of viral particles. Like its alpha- and beta-herpesviral homologs, ORF42 is a late protein that accumulates in the viral particles. However, unlike its homologs, ORF42 is required for efficient accumulation of late viral proteins and may potentiate post-transcriptional stages of gene expression. These results demonstrate that ORF42 has an important role in KSHV replication and may contribute to shaping viral gene expression.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Biochemistry.; Advisor: Marta Gaglia.; Committee: Katya Heldwein, Claire Moore, and Ralph Isberg.; Keywords: Virology, and Biology.